Feed-forward observer-based intermittent fault detection - Sedighi, Tabassom; Foote, P. D.; Sydor, Piotr (Elsevier, 2017)
This paper provided an approach to design feed-forward observer for nonlinear systems with Lipchitz nonlinearity and bounded unknown inputs (disturbances/uncertainties) to ensure the sensitivity against intermittent faults. The proposed observer design guarantees the system error stability. Some variables and scalars are also introduced to design observer's parameters, which bring more degrees of flexibility available to the designer. The designed observer is used to propose a precision fault detection scheme including adaptive threshold design to detect intermittent faults. The efficiency of the considered approach is examined by the intermittent failure case in the suspension system of a vehicle. Simulation results show that the accurate state estimation and fault detection are achieved successfully.
Keywords: Feed-forward observer; Error stability analysis; Intermittent fault detection; Adaptive threshold design; Mass-spring-damper system